From eye rolls to punches: experience of harm from others’ drinking amongst risky drinking adolescents across Australia - Lam, Tina; Laslett, Anne-Marie; Ogeil, R.P.; Lubman, D.I.; Liang, Wenbin; Chikritzhs, Tanya; Gilmore, William; Lenton, Simon; Fischer, J.; Aiken, A.; Mattick, R.; Burns, L.; et al. (2019)
© 2019 Sax Institute. All rights reserved. Objectives: Exploration of experience of harms due to another person’s drinking within a demographic particularly vulnerable to these consequences. Importance of study: Largest sampling of young Australian risky drinkers, who are underrepresented in general population surveys. The range of harms due to others’ drinking reported here is more comprehensive than documented elsewhere. Study type: Cross-sectional self-report survey. Methods: Participants were 14–19 years old and screened as being within the riskiest-drinking 25% for their age cohort. The convenience sample of 3465 was recruited primarily by social media advertising. Face-to-face interviews were conducted in all eight Australian capital cities (n = 596), supplemented by online surveys (n = 2869). Past 12-month experience of 13 harms due to others’ drinking was assessed by age, gender and perpetrator. Results: Females were more likely to experience seven harms, mainly characterised by fear and harassment, including being harassed or bothered at a party or some other private setting (41% vs 34% of males, p < 0.001), being given unwanted sexual attention (71% vs 47%, p < 0.001) and being put in fear (33% vs 20%, p < 0.001). Males were more likely to experience three harms, characterised by aggression: being yelled at, criticised or verbally abused (38% vs 33% of females, p = 0.002), being pushed or shoved (42% vs 28%, p < 0.001) and being physically hurt (17% vs 11%, p < 0.001). Teenagers of a legal alcohol-purchase age were more likely to experience harassment in public settings (49% vs 32–34%, p < 0.001) and unwanted sexual attention (66% vs 51–59%, p < 0.001) compared with younger teenagers. Seven of the harms studied were more likely (p < 0.01) to be perpetrated by people the respondents knew, and five (those associated with fear and aggression) were more likely to be perpetrated by strangers. Conclusion: Young people who are risky drinkers commonly experience multiple harms from others’ drinking. Many of these alcohol harms to others are reported here for the first time, as previous studies of adolescent drinking have focused almost exclusively on the harms young people have experienced from their own drinking. This refocusing on the harms caused by the drinking of others may prompt greater community concern and concomitant calls for better alcohol regulation.